2015
DOI: 10.1186/s12889-015-2319-8
|View full text |Cite
|
Sign up to set email alerts
|

What makes health impact assessments successful? Factors contributing to effectiveness in Australia and New Zealand

Abstract: BackgroundWhile many guidelines explain how to conduct Health Impact Assessments (HIAs), less is known about the factors that determine the extent to which HIAs affect health considerations in the decision making process. We investigated which factors are associated with increased or reduced effectiveness of HIAs in changing decisions and in the implementation of policies, programs or projects. This study builds on and tests the Harris and Harris-Roxas’ conceptual framework for evaluating HIA effectiveness, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 23 publications
1
57
0
3
Order By: Relevance
“…Findings from this study were similar to those from HIA evaluations conducted in Europe (Davenport, 2006;Wismar, 2007) and in Australia (Haigh, 2013). Several studies have specifically documented facilitators and barriers to successful HIAs (Davenport, 2006;Bourcier, 2015: Haigh, 2015Dannenberg, 2016 (Pollack, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Findings from this study were similar to those from HIA evaluations conducted in Europe (Davenport, 2006;Wismar, 2007) and in Australia (Haigh, 2013). Several studies have specifically documented facilitators and barriers to successful HIAs (Davenport, 2006;Bourcier, 2015: Haigh, 2015Dannenberg, 2016 (Pollack, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Davenport et al (32) reported on all HIAs identified in multiple databases as of 2004. The other reports purposefully selected HIAs from large databases by using criteria such as having “some potential for effectiveness” (35): reflecting diversity in sector, geography, timing, effectiveness, and funding (31,33): or relating to the agency’s mission (34). HIAs were examined from such sectors as land use, transportation, housing, agriculture, energy, health services, and waste management.…”
Section: Resultsmentioning
confidence: 99%
“…For example Kearney (Kearney, 2004) in an evaluation of community participation in a regenerartion HIA found that "The results suggest that there may be a large gap between professional rhetoric and the reality of community participation, and that barriers to community participation in HIA may be substantial and institutionalised" Community participation is often considered as a central practice for effective HIAs (den Broeder, Uiters, ten Have, Wagemakers, & Schuit, 2017;Mahoney, Potter, & Marsh, 2007). The presence of local residential involvement and contribution in HIAs has been shown to have a positive impact on the success of projects from development through to implementation (Chadderton, Elliott, Hacking, Shepherd, & Williams, 2012;Chilaka, 2015;den Broeder et al, 2017;Elliott & Williams, 2008;Haigh et al, 2015;Wright, Parry, & Mathers, 2005). However, community participation is often hard to establish, and also for it to be best managed within the timeframes and expectations of policy making, which can make a truly collaborative HIA process a challenge to attain (Chadderton et al, 2012;Parry & Wright, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although engaging community members in HIAs is standard good practice, evaluations of HIAs have found variation in levels of community engagement and community perspectives are often missing or limited to providing evidence in the identification stage (Haigh et al, 2015;Schuchter, Bhatia, Corburn, & Seto, 2014).This similar to the consideration of equity in HIA, where equity is a core value and expected to be considered all HIAs however in reality is often missed or superficially considered (Povall, Haigh, Abrahams, & Scott-Samuel, 2013). Similar to the Equity Focussed HIA approach developed in Australia (Simpson, Mahoney, Harris, Aldrich, & Stewart-Williams, 2005) we felt that it would be useful to adopt an HIA approach that was explicitly grounded in the community.…”
Section: Discussionmentioning
confidence: 99%